Playing with temptation: Stopping abilities to chocolate are superior, but also more extensive. (1st February 2023) - Schroeder, Philipp A.; Mayer, Katja; Wirth, Robert; Svaldi, Jennifer
Abstract: Cue-specific inhibitory control is assumed to support balanced food intake, but previous studies with established measures showed inconsistent results. We developed a novel kinematic stop task in virtual reality (VR) and report results from trajectory recordings. The primary objective of this explorative study was to assess the interrelationships between validated measures of food-related inhibitory control and novel measures from the VR task. We hypothesized that healthy female participants show worse inhibitory control when grasping attractive virtual chocolate, compared to non-edible color-and-shape matched objects. We further aimed to quantify the construct validity of kinematic measures (e.g., reaching extent/spatial displacement, movement time after stop-signal, velocity) with established measures of inhibitory control in a keyboard-based adaptive stop-signal task (SST). In total, 79 females with varying levels of chocolate craving participated in an experimental study consisting of self-report questionnaires, subjective chocolate craving, the conventional SST and the kinematic task in VR. Results showed superior stopping ability to chocolate in both tasks. In VR, participants successfully interrupted an initiated approach trajectory but terminated slightly closer to chocolate targets. Stop-signal delay (SSD) was adapted relative to movement onset and appeared later in chocolate trials, during which participants still stopped faster, as was also confirmed by shorter stop-signal reaction time (SSRT) in the conventional task. Yet, SSRT did not correlate with stopping in VR. Moreover, SSRT was related to depressive symptoms whereas measures from VR were related to chocolate craving and subjective hunger. Thus, VR stopping can provide deeper insights into healthy weight individuals' capacity to inhibit cue-specific approach behavior towards appetitive stimuli in simulated interactions. Furthermore, the results support a multi-faceted view of food-specific inhibitory control and behavioral impulsivity.